Analysis of heterocyclic aromatic amine profiles in Chinese traditional bacon and sausage based on ultrahigh-performance liquid chromatography–quadrupole-Orbitrap high-resolution mass spectrometry (UHPLC–Q-Orbitrap-HRMS). (25th April 2020) - Dong, Hao; Xian, Yanping; Li, Haixia; Wu, Yuluan; Bai, Weidong; Zeng, Xiaofang
Highlights: An SPE–UHPLC–Q-Orbitrap HRMS approach was developed for HAA analysis. Data-dependent scan of Q-Orbitrap provides product ion spectra with accurate mass. 14 HAAs were effectively extracted and purified by Strata TM -X-C SPE cartridge. Harman and norharman were widely found in bacon and sausage. Abstract: Ultrahigh-performance liquid chromatography coupled to quadrupole Orbitrap high-resolution mass spectrometry (UHPLC–Q-Orbitrap-HRMS) was used for the screening and determination of 14 heterocyclic aromatic amines (HAAs) in Chinese traditional bacon and sausage. HAAs were extracted from samples using sodium hydroxide solution with acetonitrile, and purified by solid-phase extraction. UHPLC–Q-Orbitrap-HRMS acquired full MS data for quantification, and UHPLC–Q-Orbitrap-Full MS/dd-MS2 (i.e., data-dependent scan mode) obtained product ion spectra for identification. Quantification was achieved using matrix-matched standard calibration curves along with the use of isotope labeled standards as internal standards. Linearity was observed in the range of 0.2–500 μg/L for 14 HAAs, with determination coefficients ( R 2 ) greater than 0.997. Limits of detection and limits of quantification were in the ranges of 0.1–0.8 μg/kg and 0.3–2.5 μg/kg, respectively. UHPLC–Q-Orbitrap-HRMS demonstrated acceptable performance for quantification and confirmation of HAAs, while UHPLC–Q-Orbitrap-Full MS/dd-MS2 along with library matching showed great potential for screening and confirmation of unknown HAAs in meat products.